Methods of Forming Pupils’ Linguistic Competence While Studying Morphology in General Secondary Educational Establishments in the Ukrainian Danube Region: Array - Glushchuk, Svitlana (Journal of Danubian Studies and Research, 2020)
The article deals with the methods of forming pupils’ stylistic competence while studying morphology of the Russian language in general secondary educational establishments of the Ukrainian Danube region. We analyzed the specific features of teaching this section of linguistics in the Ukrainian school, which include the necessity of strengthening the practical approach in training, studying on the basis of generalized morphological concepts (parts of speech, morphological features), studying morphology on a syntactic basis, and also taking into account the specifics of mastering the morphological phenomena of Russian in close relation to the Ukrainian language. We presented the system of studying at school the parts of speech and their forms: the general notion of the parts of speech, the concept about the notional and structural parts of speech, their morphological qualities, special features of parts of speech inflections and ways of word formation.